An Observational Study to Assess the Effectiveness of 4CMenB against Meningococcal Disease and Carriage and Gonorrhea in Adolescents in the Northern Territory, Australia—Study Protocol - Helen S. Marshall; Prabha H. Andraweera; James Ward; John Kaldor; Ross Andrews; Kristine Macartney; Peter Richmond; Vicki Krause; Ann Koehler; David Whiley; Lynne Giles; Rosalind Webby; et al. (Vaccines, 2022)
Invasive meningococcal disease (IMD) causes significant morbidity and mortality worldwide with serogroup B being the predominant serogroup in Australia and other countries for the past few decades. The licensed 4CMenB vaccine is effective in preventing meningococcal B disease. Emerging evidence suggests that although 4CMenB impact on carriage is limited, it may be effective against gonorrhoea due to genetic similarities between Neisseria meningitidis and Neisseria gonorrhoeae. This study protocol describes an observational study that will assess the effect of the 4CMenB vaccine against meningococcal carriage, IMD and gonorrhoea among adolescents in the Northern Territory (NT). All 14–19-year-olds residing in the NT with no contraindication for 4CMenB vaccine will be eligible to participate in this cohort study. Following consent, two doses of 4CMenB vaccine will be administered two months apart. An oropharyngeal swab will be collected at baseline and 12 months to detect pharyngeal carriage of Neisseria meningitidis by PCR. The main methodological approaches to assess the effect of 4CMenB involve a nested case control analysis and screening method to assess vaccine effectiveness and an Interrupted Time Series regression analysis to assess vaccine impact. Research ethics approvals have been obtained from Menzies and Central Australian Human Research Ethics Committees and the Western Australian Aboriginal Health Ethics Committee. Results will be provided in culturally appropriate formats for NT remote and regional communities and published in international peer reviewed journals. ClinicalTrials.gov Identifier: NCT04398849.